Comparative analysis of methods for cutting spur gears based on technical and economic parameters - Hrytsai, Ihor; Herus, Dmytro; Hromniuk, Serhii (Видавництво Львівської політехніки, 2024)
The results of the simulation and study of the process of cutting gears by the traditional method of hobbing and the new radial-circular method (RCM), which is carried out by a thin disk cutter, but in the conditions of continuous profile generation, as it is in gear cutting with a hob. It has been shown that due to the peculiarities of this process, its kinematics, and the structure of the disk cutter, RCM is superior to hobbing in all the parameters studied: volumetric productivity, chip thickness ratio, and cutting forces, machining time and machining costs. The higher efficiency of the radial-circular method has thus been demonstrated and the feasibility of its practical application has been confirmed.
Keywords: spur gear; radial-circular method; gear cutting; thin disc cutter; chip; cutting force